2017
DOI: 10.1016/j.yrtph.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cardiovascular and pulmonary function endpoints and other physiological effects following partial or complete substitution of cigarettes with electronic cigarettes in adult smokers

Abstract: Acute changes in select physiological parameters associated with cardiovascular physiology (systolic and diastolic blood pressure (BP) and heart rate (HR)), pulmonary function (FVC, FEV1, and exhaled CO and NO) and adverse events were measured in 105 clinically confined subjects who were randomized into groups that either completely or partially switched from conventional cigarettes to e-cigarettes or completely discontinued using tobacco and nicotine products altogether. Use of the e-cigarettes for five days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 55 publications
1
43
1
1
Order By: Relevance
“…This is a useful design for assessing the respiratory effects of e-cigarettes; although some studies have found that e-cigarette users experience improvements in lung health, results have not been consistent even when users were able to reduce cigarette consumption 37383940. Studies funded by the tobacco industry have consistently found few adverse respiratory health outcomes in smokers transitioning to e-cigarette use 414243. An important caveat to these studies is that in general they have not looked at whether e-cigarettes have respiratory toxicity but at whether the measured outcomes differ from those of people exposed to ongoing cigarette smoke.…”
Section: Human Studiesmentioning
confidence: 99%
“…This is a useful design for assessing the respiratory effects of e-cigarettes; although some studies have found that e-cigarette users experience improvements in lung health, results have not been consistent even when users were able to reduce cigarette consumption 37383940. Studies funded by the tobacco industry have consistently found few adverse respiratory health outcomes in smokers transitioning to e-cigarette use 414243. An important caveat to these studies is that in general they have not looked at whether e-cigarettes have respiratory toxicity but at whether the measured outcomes differ from those of people exposed to ongoing cigarette smoke.…”
Section: Human Studiesmentioning
confidence: 99%
“…These studies reported HR and BP outcomes, summarized in the following paragraph and in ESM Table 3. Only one of these studies was a short-term (5 day) switch study [11] during which the participants were confined and smoking behavior was monitored. In total, 105 chronic TC smokers were randomized to three general groups: (1) TC to EC complete switch; (2) TC to EC switch but TCs were allowed; (3) complete TC and nicotine cessation.…”
Section: Chronic Autonomic Cardiovascular Effects Of Switching From Cmentioning
confidence: 99%
“…In a study of 23 daily e-cigarette users, e-cigarette power output was reported to vary between 5 and 60 W, puff volume varied between 10-251 mL, and puff duration between 1.3 and 5.8 s [19]. Understanding of the relative importance of different parameters affecting e-cigarette emissions is needed for formulating standardized testing protocols and translating laboratory results to real-life exposure.Carbon monoxide (CO) emissions from e-cigarette have been understudied [20,21], because a few studies showed that exhaled CO concentrations among e-cigarette users were significantly lower than conventional tobacco smokers [7,[22][23][24]. However, CO can be formed in e-cigarettes through thermal decomposition of e-liquid base materials (propylene glycol (PG) and vegetable glycerin (VG)) [25] and some flavoring compounds [26].…”
mentioning
confidence: 99%
“…Carbon monoxide (CO) emissions from e-cigarette have been understudied [20,21], because a few studies showed that exhaled CO concentrations among e-cigarette users were significantly lower than conventional tobacco smokers [7,[22][23][24]. However, CO can be formed in e-cigarettes through thermal decomposition of e-liquid base materials (propylene glycol (PG) and vegetable glycerin (VG)) [25] and some flavoring compounds [26].…”
mentioning
confidence: 99%